Kajian Blansing dan Metode Pengeringan Terhadap Komponen Bioaktif dan Aktivitas Antioksidan Sayuran Kering Gonda (Spenoclea zeylanica) - Nica Dewi, Putu Julyantika; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p17, 2023)
The urgency of this research is that dried gonda vegetables can support the potential of gonda vegetables as a functional food in addition to modernization demands that want to enjoy fresh vegetables at any time because they have been made in the form of dried vegetables which are certainly more extractive, efficient and have a longer shelf life. This study was designed with a Complete Randomized Design with two factors. The first factor is the preliminary treatment (blanching and without blanching), and the second is the drying method (oven (temperature 50OC for 2 hours) and microwave oven (power 350 watts – 800watts for 5 minutes)). The treatment was repeated 3 times so that 12 experimental units were obtained. The data were analyzed statistically using the variance test and if the treatment had a significant effect on the observed variables, it was continued with Tukey Multiple Range Test. The results showed that the preliminary treatment had a very significant effect (P?0.01) on flavonoids, vitamin C, tannins, and antioxidant activity, and had a significant effect (P?0.05) on yield. The drying method treatment had a very noticeable effect (P?0.01) on tannins, and had a significant effect (P?0.05) on flavonoids. The interaction between the preliminary treatment and the drying method significantly affected tannins and antioxidant activity (P?0.01). The results showed that blanching treatment with oven drying method (temperature 50OC for 2 hours) was the best treatment with water content 13.34%, yield 12.84%, rehydration ratio 115.49%, flavonoids 0.0569 mg/g, vitamin C 0.1734 mg/g, tannins 0.45 mg/g, the antioxidant activity of 62.64 mg/g, as well as the sensory assessment of color are normal with bright characteristics, texture normal with slightly soft characteristics, and overall acceptability was normal.